Flood Hazard Risk Assessment based on Multi-criteria Spatial Analysis GIS as Input for Spatial Planning Policies in Tegal Regency, Indonesia - Sejati, Anang Wahyu; Putri, Savira Nur Afifah Kusuma; Rahayu, Sri; Buchori, Imam; Rahayu, Kristantri; Wiratmaja, I Gusti A.M. Andika; Muzaki, Ahmad Jihan; Basuki, Yudi (Geographica Pannonica, 2023)
Recent discussions on flood disasters concern the risk factors and causes between nature and anthropogenic activities. This disaster requires serious handling, which needs to be analyzed, especially in areas affected by flooding in the Tegal Regency, Indonesia, as a case study. The weakness of the existing mitigation efforts is still needed to be comprehensive, requiring a multi-criteria assessment based on GIS spatial analysis. The method used is a raster calculator and weighted superimpose by setting several calculation variables from both physical and non-physical aspects to support the multi-criteria spatial analysis. The results show that spatially, more than 30% of areas with a high-risk index are located in the downstream or coastal regions of Tegal Regency. However, the index of capacity and resilience in several flood-affected sub-districts is at an index above 0.5, so they have good strength to disasters such as the four sub-districts of Adiwerna, Bumijawa, Bojong, and Kramat. From the analysis results, land use change is the biggest problem that affects the number of the flood event. With this condition, the appropriate mitigation effort for Tegal Regency is strengthening the spatial planning policy and increasing the capacity, especially in disaster governance in a high-risk area. Thus, the vulnerability and hazard factors will be anticipated with high community participation in strengthening the capacity index.
Keywords: GIS spatial analysis; Flood disaster; Capacity Index; Land Use change